2020
DOI: 10.5507/bp.2019.006
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of resveratrol on acute kidney injury in rats with sepsis

Abstract: Aim. To evaluate the protective effects of resveratrol on acute kidney injury (AKI) in septic rats. Methods. A septic rat model was established by cecal ligation and puncture (CLP). A total of 108 male Sprague Dawley rats were randomly divided into an observation group, a 6 h resveratrol intervention group and a 12 h resveratrol intervention group. Then each group was subdivided into Sham, Sham + Res, CLP and CLP + Res groups. After surgery, the survival and morphological changes in kidney tissues were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
(22 reference statements)
1
23
0
Order By: Relevance
“…In this study, resveratrol treatment reversed the increased levels of IL-1β, IL-6, and TNF-α in kidney tissue and serum under hyperuricemic conditions, indicating that regulation of the inflammatory response may be a crucial part of resveratrol protecting against hyperuricemic nephropathy. Additionally, resveratrol has been demonstrated to alleviate acute kidney injury in lipopolysaccharide-treated mice [16] and to reduce the serum levels of TNF-α, IL-1β, and IL-6 in septic rats [17][18][19]. However, nuclear factor (NF)-related factor 2 signaling also has been shown to be regulated by resveratrol in https://doi.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, resveratrol treatment reversed the increased levels of IL-1β, IL-6, and TNF-α in kidney tissue and serum under hyperuricemic conditions, indicating that regulation of the inflammatory response may be a crucial part of resveratrol protecting against hyperuricemic nephropathy. Additionally, resveratrol has been demonstrated to alleviate acute kidney injury in lipopolysaccharide-treated mice [16] and to reduce the serum levels of TNF-α, IL-1β, and IL-6 in septic rats [17][18][19]. However, nuclear factor (NF)-related factor 2 signaling also has been shown to be regulated by resveratrol in https://doi.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol upregulates PGC-1α, NRF1, NRF2 and Tfam leading to potentiation of mitochondrial biogenesis (100). In multiple studies using a CLP model of polymicrobial sepsis in rats, resveratrol treatment results in increased survival as well as decreased kidney injury associated with inhibition of NFκB (101,102). In a similar model of pediatric sepsis-induced kidney injury in young rats, resveratrol was shown to activate NRF2 and protect from injury (103).…”
Section: Natural Products That Induce Mitochondrial Biogenesismentioning
confidence: 98%
“…Hence, the effect of resveratrol has been evaluated in AKI cases to determine its ameliorative properties, as well as its underlying molecular mechanisms. In separate studies, Wang et al and Luo et al showed that resveratrol reduced LPS‐mediated increases in pro‐inflammatory cytokines (IL‐6, IL‐1β, and TNF‐α) by suppressing the inositol‐requiring enzyme 1 (IRE1)‐NF‐κB pathway 62,63 . Moreover, resveratrol was shown to increase the levels of the anti‐inflammatory cytokine, IL‐10, in AKI 63 .…”
Section: Treatment Of Sepsis With Polyphenolic Compoundsmentioning
confidence: 99%
“…In separate studies, Wang et al and Luo et al showed that resveratrol reduced LPS‐mediated increases in pro‐inflammatory cytokines (IL‐6, IL‐1β, and TNF‐α) by suppressing the inositol‐requiring enzyme 1 (IRE1)‐NF‐κB pathway 62,63 . Moreover, resveratrol was shown to increase the levels of the anti‐inflammatory cytokine, IL‐10, in AKI 63 . Resveratrol has also been reported to exert protective effects against sepsis‐associated encephalopathy (SAE) by inhibiting the NLRP3/IL‐1𝛽 axis in LPS‐stimulated microglial cells in the hippocampus of SAE mice 64 .…”
Section: Treatment Of Sepsis With Polyphenolic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation